Favorable elements for the reading comprehension of texts in english in a virtual course - Osnaya-Moreno, Mabel; Llanes-Medina, Arnoldo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objective of this study was to promote reading comprehension (CL) of texts in the English language in 12 Spanish-speaking students with level A2 of the MCE. To achieve this objective, we worked with a virtual course composed of the PPP teaching methodology, applied practical situations, analysis of the cognitive processes underlying the exercises by the participants, continuous feedback and, all of this, under the interactive reading model. . The evaluation of the CL was done before and after the course. The result was ten participants who passed the MCE level B1 reading comprehension exam.